Internalisasi Nilai Karakter Santriwati melalui Program Fiqhunnisa: Studi Kasus di Pondok Modern Darussalam Gontor Putri 1 - Arly Zahra Maulida; Cecep Sobar Rochmat; Idam Mustofa; Syarifah Syarifah (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2026)
This study aims to describe the process of internalising character values among female students through the Fiqhunnisa Programme at Pondok Modern Darussalam Gontor Putri 1, as well as to identify the character values instilled in the programme. The Fiqhunnisa Programme is a learning activity designed to equip female students with an understanding of women’s fiqh whilst instilling Islamic character values relevant to daily life. This study employs a qualitative approach using a case study design. Data were collected through observation, in-depth interviews with mentors and female students, and documentation of activities. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions, whilst data validity was tested using source and method triangulation techniques. The research findings indicate that the internalisation of character values within the Fiqhunnisa Programme is carried out through several stages, namely the imparting of an understanding of values, setting a good example, habit formation, supervision, and evaluation. The character values internalised include religiosity, responsibility, discipline, positive modesty, politeness, cleanliness, and self-awareness as Muslim women. The internalisation of these values takes place not only through the delivery of material but also through direct practice in the daily lives of the female students within the boarding school environment. The Fiqhunnisa programme contributes to shaping the character of female students so that they possess noble morals, understand their role and identity as women in accordance with Islamic teachings, and are able to implement these values in both their personal and social lives.